Meta‐analysis and meta‐regression analysis of biomarkers for abdominal aortic aneurysm. Issue 11 (18th August 2014) - Stather, P. W.; Sidloff, D. A.; Dattani, N.; Gokani, V. J.; Choke, E.; Sayers, R. D.; Bown, M. J.
Abstract Background Many studies have investigated the systemic and local expression of biomarkers in patients with abdominal aortic aneurysm (AAA). The natural history of AAA varies between patients, and predictors of the presence and diameter of AAA have not been determined consistently. The aim of this study was to perform a systematic review, meta‐analysis and meta‐regression of studies comparing biomarkers in patients with and without AAA, with the aim of summarizing the association of identified markers with both AAA presence and size. Methods and results Literature review identified 106 studies suitable for inclusion. Meta‐analysis demonstrated a significant difference between matrix metalloproteinase (MMP) 9, tissue inhibitor of matrix metalloproteinase 1, interleukin (IL) 6, C‐reactive protein (CRP), α1‐antitrypsin, triglycerides, lipoprotein(a), apolipoprotein A and high‐density lipoprotein in patients with and without AAA. Although meta‐analysis was not possible for MMP‐2 in aortic tissue, tumour necrosis factor α, osteoprotegerin, osteopontin, interferon γ, intercellular cell adhesion molecule 1 and vascular cell adhesion molecule 1, systematic review suggested an increase in these biomarkers in patients with AAA. Meta‐regression analysis identified a significant positive linear correlation between aortic diameter and CRP level. Conclusion A wide variety of biomarkers are dysregulated in patients with AAA, but their clinical value is yet to be established. Future research should focus on the most relevant biomarkers of AAA, and how they could be used clinically.